Do timing of injection and status of the suction drain effect postoperative pain scores after intra-articular bupivacaine injection in arthroscopic ACL reconstruction? - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2015)
Objective: The aim of this study was to determine if the timing of intra-articular local anesthetic injection and the status of the suction drain affect variable pain scores after ACL reconstruction. Methods: The study included 40 patients undergoing arthroscopic ACL reconstruction randomized into 4 groups. Patients in Group 1 received intra-articular 20 ml of 0.25% bupivacaine 20 minutes before the start of the operation (preemptive: PE), Group 2 at the end of the operation with the suction drain opened (DO). Group 3 also received intra-articular bupivacaine at the end of the operation and the drain was kept closed for one hour postoperatively (DC). Group 4 did not receive any intra-articular injection (control group: CG) and served as the control group. Visual analog scale (VAS) scores and additional analgesic requirements were recorded. Results: The PE group had the lowest and the control group the highest VAS scores at the second postoperative hour. At the fourth postoperative hour, VAS scores were significantly higher in the DC group than the DO group (p<0.05). At the sixth postoperative hour, the PE and DC groups had significantly lower VAS scores than the other groups (p<0.05). At Hour 12, the PE and control groups had higher VAS scores than the DO and DC groups. VAS scores were not different among groups at Hour 24. The interval to first analgesic requirement was significantly shorter in the control group and longer in the PE group in comparison to the other two groups (p<0.001). Conclusion: Intra-articular bupivacaine injection at different stages of the operation yielded variable VAS scores in the postoperative period. Closing the drain after intra-articular injection resulted in an early onset analgesic effect without shortening the duration.
Keywords: ACL reconstruction; bupivacaine; drain; postoperative pain; VAS score; CRUCIATE LIGAMENT RECONSTRUCTION; 0.5-PERCENT BUPIVACAINE; ARTICULAR CHONDROCYTES; KNEE SURGERY; MORPHINE; INFILTRATION; MANAGEMENT; ANESTHESIA; ANALGESIA; BLOCK